A high-strength and high-conductivity copper alloy containing tantalum and a preparation method thereof
Patent Information
- Application Number
- CN202611413435.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-11
- Publication Date
- 2026-10-27
AI Technical Summary
[0004]本发明的目的在于提供一种含钽高强高导铜合金及其制备方法,用于解决现有高温铜合金难以兼顾高温强度、热导率与加工性能的技术问题
[0004]本发明的目的在于提供一种含钽高强高导铜合金及其制备方法,用于解决现有高温铜合金难以兼顾高温强度、热导率与加工性能的技术问题。有鉴于此,本发明通过以下方案予以实现。
Smart Images

Figure CN122979699A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of high-strength, high-conductivity copper alloy technology, and more specifically, to a tantalum-containing high-strength, high-conductivity copper alloy and its preparation method. Background Technology
[0002] Copper alloys, due to their excellent electrical and thermal conductivity, are widely used in high heat flux density components such as combustion chamber linings of liquid rocket engines. These service environments require materials to possess good room-temperature machinability, high-temperature strength and resistance to softening at 500–700°C, and high thermal conductivity. However, pure copper lacks sufficient high-temperature strength, and conventional precipitation-strengthened copper alloys such as Cu-Cr-Zr and Cu-Ni-Si exhibit performance degradation due to the easy dissolution and coarsening of the strengthening phase within the target temperature range, making it difficult to meet these stringent requirements.
[0003] In recent years, Cu-Cr-Nb high-temperature copper alloys have been developed, achieving high-temperature strengthening by introducing a thermally stable Cr2Nb-type Laves phase into a highly conductive Cu matrix. However, these alloys still face a significant strength-thermal conductivity contradiction. Increasing the Cr and Nb content to increase the volume fraction of the strengthening phase leads to an increase in residual solid solution atoms and a significant increase in phase interfaces in the Cu matrix, exacerbating electron and phonon scattering and resulting in a significant decrease in thermal conductivity. Simultaneously, solidification segregation easily forms coarse or continuous network-like second phases, impairing processing plasticity. Furthermore, Nb has extremely low solubility in Cu, making uniform dissolution difficult to achieve in conventional single-melting processes. Existing research has shown that introducing Ta to replace some Nb sites in the formation of the Laves phase may help suppress second-phase coarsening using its high stability. However, if the Ta addition amount and the Cr / (Nb+Ta) atomic ratio are not properly controlled, undissolved particles or brittle phases can easily form, which in turn worsens processing performance and thermal conductivity. Summary of the Invention
[0004] The purpose of this invention is to provide a tantalum-containing high-strength, high-conductivity copper alloy and its preparation method, to solve the technical problem that existing high-temperature copper alloys struggle to simultaneously achieve high-temperature strength, thermal conductivity, and processing performance. Therefore, this invention is achieved through the following solution.
[0005] In a first aspect, the present invention provides a high-strength, high-conductivity copper alloy containing tantalum, comprising, by mass percentage: 2.60~3.00 wt.% chromium, 2.00~2.50 wt.% niobium, 0.30~0.50 wt.% tantalum, with the balance being copper and unavoidable impurities; in this alloy, the atomic ratio of chromium to the sum of niobium and tantalum is 2.00~2.10, and the atomic fraction of tantalum in the sum of niobium and tantalum is 0.05~0.12.
[0006] Compared with the prior art, in the tantalum-containing high-strength and high-conductivity copper alloy of the present invention, by limiting the mass fractions of chromium, niobium and tantalum to 2.60~3.00wt.%, 2.00~2.50wt.% and 0.30~0.50wt.% respectively, and simultaneously constraining the atomic ratio R of chromium to the sum of niobium and tantalum to 2.00~2.10 and the atomic fraction of tantalum in the sum of niobium and tantalum to 0.05~0.12, it is beneficial to improve the comprehensive matching of high-temperature strength and thermal conductivity of the alloy under low total alloying conditions. Specifically, the high-temperature performance of existing Cu-Cr-Nb alloys relies on the precipitation of Cr2Nb-type Laves phase in the copper matrix. However, this system has a fundamental contradiction between strength and thermal conductivity: increasing the Cr and Nb content can increase the volume fraction of the strengthening phase to obtain higher high-temperature strength, but it will inevitably lead to an increase in the number of residual solid solution atoms in the copper matrix and a significant increase in the density of the interface between the second phase and the matrix. Both of these will exacerbate the scattering of conduction electrons and phonons, resulting in a significant decrease in thermal conductivity. At the same time, excessive second phase will still coarsen under high-temperature service conditions, weakening the strengthening effect and impairing processing plasticity. Conventional approaches can only make trade-offs in this contradiction and cannot achieve a simultaneous improvement in high-temperature strength and thermal conductivity. The present invention addresses the aforementioned contradiction primarily through the precise constraint of the atomic ratio R. As an AB2-type intermetallic compound, the Laves phase's chemical composition and physical properties are extremely sensitive to the relative proportions of the A and B sites. When the R value deviates from 2.00, this deviation from the stoichiometric ratio results in free chromium or residual refractory elements that cannot fully enter the Laves phase lattice and remain in the copper matrix, causing localized lattice distortion and scattering of conduction electrons, thus impairing thermal conductivity. The present invention, by strictly limiting the R value to a window approaching the ideal stoichiometric ratio of 2.00 to 2.10, promotes the existence of Cr, Nb, and Ta in the form of the Cr2(Nb,Ta) type Laves phase and reduces the residual solute content in the Cu matrix, creating conditions for maintaining higher thermal conductivity. Based on this, the present invention introduces a specific proportion of tantalum to modify the Laves phase in situ. Tantalum and niobium are both refractory metal elements, and tantalum is miscible with niobium in the Cr2Nb lattice. The atomic fraction of tantalum in the sum of niobium and tantalum is limited to 0.05~0.12, that is, tantalum replaces about 5~12 at.% of niobium sites, allowing tantalum atoms to directly dissolve into the Laves phase lattice of Cr2Nb to form a Cr2(Nb,Ta) composite Laves phase. Compared with Nb, Ta has a higher melting point (Ta is 3017℃, Nb is 2477℃). After replacing Nb sites, Ta's suppression of high-temperature diffusion and second-phase coarsening improves the high-temperature microstructure stability. Through the above technical solution of the present invention, the technical problem of existing high-temperature copper alloys being unable to simultaneously achieve high-temperature strength, thermal conductivity, and processing performance is solved.
[0007] Furthermore, in the tantalum-containing high-strength and high-conductivity copper alloy of the present invention, the total content of chromium, niobium and tantalum is 5.00~5.80 wt.%; the strengthening phase in the alloy is a Cr2(Nb,Ta) type composite Laves phase.
[0008] Furthermore, in the tantalum-containing high-strength and high-conductivity copper alloy of the present invention, the atomic ratio of chromium to the sum of niobium and tantalum is 2.03 to 2.07.
[0009] Secondly, the present invention provides a method for preparing a tantalum-containing high-strength, high-conductivity copper alloy, comprising: Weigh out the raw materials of copper, chromium, niobium and tantalum according to the proportions; Take 5-15% of the total mass of copper and melt it with all chromium, niobium and tantalum, and solidify it. Turn the resulting pre-alloyed ingot over and melt it again 3-4 times to obtain the pre-alloyed ingot. The pre-alloyed ingot is melted together with the remaining copper and solidified. The resulting ingot is then flipped over and melted repeatedly 5 to 6 times to obtain the final ingot. The ingot is subjected to multiple warm rolling passes at 300~450℃ to obtain warm rolled sheet; The warm-rolled sheet is subjected to aging heat treatment at 450~550℃, held at that temperature for 0.5~4h, and then rapidly cooled to room temperature to obtain the tantalum-containing high-strength and high-conductivity copper alloy.
[0010] Compared with the prior art, the beneficial effects of the preparation method of the tantalum-containing high-strength and high-conductivity copper alloy of the present invention are the same as those of the tantalum-containing high-strength and high-conductivity copper alloy described in the above technical solution, and will not be repeated here.
[0011] Furthermore, in the preparation method of the tantalum-containing high-strength and high-conductivity copper alloy of the present invention, the total content of chromium, niobium and tantalum in the tantalum-containing high-strength and high-conductivity copper alloy is 5.00~5.80 wt.%; the strengthening phase in the alloy is a Cr2(Nb,Ta) type composite Laves phase.
[0012] Furthermore, in the preparation method of the tantalum-containing high-strength and high-conductivity copper alloy of the present invention, when 5-15% of the total mass of copper is smelted with all chromium, niobium and tantalum, the arc power is increased in a stepwise manner during smelting, and the reference temperatures of the molten pool surface are successively 1150-1250℃, 1450-1550℃ and 1800-1900℃, and are held for 5-15 seconds, 5-15 seconds and 20-40 seconds respectively.
[0013] Furthermore, in the preparation method of the tantalum-containing high-strength and high-conductivity copper alloy of the present invention, the melting process adopts a stepped heating method, with the reference temperatures on the surface of the molten pool being 1150~1250℃, 1400~1500℃ and 1650~1780℃ respectively; during the last 1~2 remeltings, the reference temperature on the surface of the molten pool is controlled at 1650~1720℃.
[0014] Furthermore, in the preparation method of the tantalum-containing high-strength and high-conductivity copper alloy of the present invention, the single-pass reduction rate of the multi-pass warm rolling is 5~12%, the total reduction rate is 60~75%, and the furnace is held for 3~5 minutes after each rolling pass; the temperature of warm rolling is 300~450℃.
[0015] Furthermore, in the preparation method of the tantalum-containing high-strength and high-conductivity copper alloy of the present invention, the rapid cooling is water cooling; the aging heat treatment is carried out in a vacuum or inert atmosphere.
[0016] Thirdly, the present invention provides the application of the above-mentioned tantalum-containing high-strength and high-conductivity copper alloy in the regenerative cooling combustion chamber lining of liquid rocket engines or in high heat flux density components at 500~700°C. Attached Figure Description
[0017] The accompanying drawings, which are included to provide a further understanding of the invention and form part of this invention, illustrate exemplary embodiments of the invention and are used to explain the invention, but do not constitute an undue limitation of the invention. In the drawings: Figure 1 This is a schematic flowchart of a method for preparing a tantalum-containing high-strength and high-conductivity copper alloy according to the present invention. Detailed Implementation
[0018] To make the technical problems to be solved, the technical solutions, and the beneficial effects of the present invention clearer, the present invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative of the present invention and are not intended to limit the present invention.
[0019] It should be noted that when a component is referred to as being "fixed to" or "set on" another component, it can be directly on or indirectly on that other component. When a component is referred to as being "connected to" another component, it can be directly connected to or indirectly connected to that other component.
[0020] Furthermore, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of indicated technical features. Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more of that feature. In the description of this invention, "a plurality of" means two or more, unless otherwise explicitly specified. "Several" means one or more, unless otherwise explicitly specified.
[0021] In recent years, Cu-Cr-Nb high-temperature copper alloys have been developed, achieving high-temperature strengthening by introducing a thermally stable Cr2Nb-type Laves phase into a highly conductive Cu matrix. However, these alloys still face a significant strength-thermal conductivity contradiction. Increasing the Cr and Nb content to increase the volume fraction of the strengthening phase leads to an increase in residual solid solution atoms and a significant increase in phase interfaces in the Cu matrix, exacerbating electron and phonon scattering and resulting in a significant decrease in thermal conductivity. Simultaneously, solidification segregation easily forms coarse or continuous network-like second phases, impairing processing plasticity. Furthermore, Nb has extremely low solubility in Cu, making uniform dissolution difficult to achieve in conventional single-melting processes. Existing research has shown that introducing Ta to replace some Nb sites in the formation of the Laves phase may help suppress second-phase coarsening using its high stability. However, if the Ta addition amount and the Cr / (Nb+Ta) atomic ratio are not properly controlled, undissolved particles or brittle phases can easily form, which in turn worsens processing performance and thermal conductivity.
[0022] To address the above technical problems, this invention provides a high-strength, high-conductivity copper alloy containing tantalum, comprising, by mass percentage: 2.60~3.00 wt.% chromium, 2.00~2.50 wt.% niobium, and 0.30~0.50 wt.% tantalum, with the balance being copper and unavoidable impurities; in this alloy, the atomic ratio of chromium to the sum of niobium and tantalum is 2.00~2.10, and the atomic fraction of tantalum in the sum of niobium and tantalum is 0.05~0.12. For example, chromium may be 2.60 wt.%, 2.80 wt.%, or 3.00 wt.%, niobium may be 2.00 wt.%, 2.25 wt.%, or 2.50 wt.%, and tantalum may be 0.30 wt.%, 0.40 wt.%, or 0.50 wt.%. The atomic ratio of chromium to the sum of niobium and tantalum may be 2.00, 2.05, or 2.10; and the atomic fraction of tantalum in the sum of niobium and tantalum may be 0.05, 0.10, or 0.12.
[0023] By adopting the above technical solution, in the tantalum-containing high-strength and high-conductivity copper alloy of the present invention, by limiting the mass fractions of chromium, niobium, and tantalum to 2.60~3.00wt.%, 2.00~2.50wt.%, and 0.30~0.50wt.%, respectively, and simultaneously constraining the atomic ratio R of chromium to the sum of niobium and tantalum to 2.00~2.10 and the atomic fraction of tantalum in the sum of niobium and tantalum to 0.05~0.12, it is beneficial to improve the comprehensive matching of high-temperature strength and thermal conductivity of the alloy under low total alloying conditions. Specifically, the high-temperature performance of existing Cu-Cr-Nb alloys relies on the precipitation of Cr2Nb-type Laves phase in the copper matrix. However, this system has a fundamental contradiction between strength and thermal conductivity: increasing the Cr and Nb content can increase the volume fraction of the strengthening phase to obtain higher high-temperature strength, but it will inevitably lead to an increase in the number of residual solid solution atoms in the copper matrix and a significant increase in the density of the interface between the second phase and the matrix. Both of these will exacerbate the scattering of conduction electrons and phonons, resulting in a significant decrease in thermal conductivity. At the same time, excessive second phase will still coarsen under high-temperature service conditions, weakening the strengthening effect and impairing processing plasticity. Conventional approaches can only make trade-offs in this contradiction and cannot achieve a simultaneous improvement in high-temperature strength and thermal conductivity. The present invention addresses the aforementioned contradiction primarily through the precise constraint of the atomic ratio R. As an AB2-type intermetallic compound, the Laves phase's chemical composition and physical properties are extremely sensitive to the relative proportions of the A and B sites. When the R value deviates from 2.00, this deviation from the stoichiometric ratio results in free chromium or residual refractory elements that cannot fully enter the Laves phase lattice and remain in the copper matrix, causing localized lattice distortion and scattering of conduction electrons, thus impairing thermal conductivity. The present invention, by strictly limiting the R value to a window approaching the ideal stoichiometric ratio of 2.00 to 2.10, promotes the existence of Cr, Nb, and Ta in the form of the Cr2(Nb,Ta) type Laves phase and reduces the residual solute content in the Cu matrix, creating conditions for maintaining higher thermal conductivity. Based on this, the present invention introduces a specific proportion of tantalum to modify the Laves phase in situ. Tantalum and niobium are both refractory metal elements, and tantalum is miscible with niobium in the Cr2Nb lattice. The atomic fraction of tantalum in the sum of niobium and tantalum is limited to 0.05~0.12, that is, tantalum replaces about 5~12 at.% of niobium sites, allowing tantalum atoms to directly dissolve into the Laves phase lattice of Cr2Nb to form a Cr2(Nb,Ta) composite Laves phase. Compared with Nb, Ta has a higher melting point (Ta is 3017℃, Nb is 2477℃). After replacing Nb sites, Ta's suppression of high-temperature diffusion and second-phase coarsening improves the high-temperature microstructure stability. Through the above technical solution of the present invention, the technical problem of existing high-temperature copper alloys being unable to simultaneously achieve high-temperature strength, thermal conductivity, and processing performance is solved.
[0024] Please see Figure 1As one possible implementation, in the tantalum-containing high-strength, high-conductivity copper alloy of the present invention, the total content of chromium, niobium, and tantalum is 5.00~5.80 wt.%; the strengthening phase in the alloy is a Cr2(Nb,Ta) type composite Laves phase. For example, the total content of chromium, niobium, and tantalum can be 5.00 wt.%, 5.50 wt.%, or 5.80 wt.%.
[0025] The present invention also provides a method for preparing a high-strength, high-conductivity copper alloy containing tantalum, comprising: weighing copper, chromium, niobium and tantalum raw materials according to the specified ratio; Take 5-15% of the total mass of copper and melt it with all chromium, niobium and tantalum, and solidify it. Turn the resulting pre-alloyed ingot over and melt it again 3-4 times to obtain the pre-alloyed ingot. The pre-alloyed ingot is melted together with the remaining copper and solidified. The resulting ingot is then flipped over and melted repeatedly 5 to 6 times to obtain the final ingot. The ingot is subjected to multiple warm rolling passes at 300~450℃ to obtain warm rolled sheet; The warm-rolled sheet is subjected to aging heat treatment at 450~550℃, held at that temperature for 0.5~4h, and then rapidly cooled to room temperature to obtain the tantalum-containing high-strength and high-conductivity copper alloy.
[0026] In the above-mentioned technical solution, the preparation method of the tantalum-containing high-strength and high-conductivity copper alloy of the present invention solves the technical problem of the difficulty in uniformly dissolving high-melting-point refractory metal elements such as chromium, niobium, and tantalum in the copper matrix by means of stepwise pre-alloying combined with multiple ingot-turning and remelting process design. Specifically, 5-15% of the total mass of copper is first melted with all the chromium, niobium, and tantalum, so that a small amount of copper acts as the molten pool medium to melt and dissolve the high-melting-point components first. After turning over and repeating the melting process 3-4 times, a pre-alloyed ingot with uniform composition is obtained. This process ensures that the refractory elements are macroscopically uniformly distributed in the pre-alloyed ingot, avoiding unmelted blocks and gravity segregation. Subsequently, the pre-alloyed ingot is melted with the remaining copper and remelted 5-6 times to further dilute the pre-alloyed metal. The refractory elements were smelted to the target composition. Simultaneously, during repeated melting, arc stirring and multiple solidification-remelting cycles effectively reduced macroscopic component segregation, ensuring the overall compositional uniformity of the ingot. Based on this, the ingot was subjected to multi-pass warm rolling at 300-450℃, combined with a deformation regime of 5-12% reduction per pass, 60-75% total reduction, and 3-5 minutes of reheating between passes. This process broke up and rearranged the as-cast second phase, and improved its distribution through plastic deformation. Finally, after aging at 450-550℃ for 0.5-4 hours, it was rapidly cooled to room temperature. The residual solid solution Cr and deformed structures further precipitated and recovered, stabilizing the second phase-matrix interface and dislocation structure. Through the synergistic combination of the above preparation method and the specific compositional range of this invention, the homogenization of the refractory elements provided a process guarantee for the precise control of the atomic ratio R, while the matching of the warm rolling and aging regimes created conditions for the dispersed distribution of the Laves phase. The embodiments of this invention demonstrate that, with a total alloying content reduced by 6.3% to 17.7% compared to the comparative example, the tantalum-containing copper alloy prepared by this method achieves excellent levels of thermal conductivity, yield strength, and tensile strength at room temperature and 600℃. This verifies the crucial supporting role of this method in achieving a synergistic match between the high-temperature strength and thermal conductivity of the alloy. Through the above-described preparation method of this invention, stable and efficient preparation of tantalum-containing high-strength and high-conductivity copper alloys is achieved, solving the technical problems of low yield and large performance fluctuations caused by the segregation of refractory elements and coarse second phases in existing preparation processes.
[0027] In one possible implementation, in the preparation method of the tantalum-containing high-strength and high-conductivity copper alloy of the present invention, when 5-15% of the total mass of copper is smelted with all chromium, niobium, and tantalum, the arc power is increased in a stepped manner during smelting. The reference temperatures of the molten pool surface are successively 1150-1250℃, 1450-1550℃, and 1800-1900℃, and held for 5-15 seconds, 5-15 seconds, and 20-40 seconds, respectively. For example, the reference temperatures of the molten pool surface can be successively 1150℃, 1450℃, and 1800℃, and the holding times can be 5 seconds, 5 seconds, and 20 seconds; or, the reference temperatures can be successively 1200℃, 1500℃, and 1850℃, and the holding times can be 10 seconds, 10 seconds, and 30 seconds, respectively; or, the reference temperatures can be successively 1250℃, 1550℃, and 1900℃, and the holding times can be 15 seconds, 15 seconds, and 40 seconds, respectively.
[0028] In one possible implementation, in the preparation method of the tantalum-containing high-strength and high-conductivity copper alloy of the present invention, the fusion process employs a stepped heating method, with the reference temperatures on the surface of the molten pool successively set at 1150~1250℃, 1400~1500℃, and 1650~1780℃; during the last 1-2 remelting stages, the reference temperature on the surface of the molten pool is controlled at 1650~1720℃. For example, the reference temperatures on the surface of the molten pool are successively set at 1150℃, 1400℃, and 1650℃, but can also be 1200℃, 1450℃, and 1700℃, or even 1250℃, 1500℃, and 1780℃.
[0029] In one possible implementation, in the preparation method of the tantalum-containing high-strength and high-conductivity copper alloy of the present invention, the single-pass reduction rate of the multi-pass warm rolling is 5-12%, the total reduction rate is 60-75%, and the furnace is held for 3-5 minutes after each rolling pass; the warm rolling temperature is 300-450°C. For example, the single-pass reduction rate can be 5%, 8%, or 12%, the total reduction rate can be 60%, 67%, or 75%, and the furnace is held for 3, 4, or 5 minutes after each rolling pass; the warm rolling temperature can be 300, 370, or 450°C.
[0030] To better understand the present invention, the following specific embodiments further illustrate the content of the present invention, but the content of the present invention is not limited to the following embodiments.
[0031] Unless otherwise specified, all raw materials used in the following examples are commercially available. Example 1
[0032] This embodiment provides a method for preparing a tantalum-containing high-strength, high-conductivity copper alloy. The raw materials are proportioned by mass percentage as follows: Cu 94.89%, Cr 2.60%, Nb 2.01%, and Ta 0.50%. The atomic ratio R of Cr to (Nb+Ta) in this composition is 2.05, and the nominal atomic fraction of Ta in (Nb+Ta) is 11.33 at.%. Step 1, Raw material preparation and batching: Select Cu particles with a purity of not less than 99.99%, and Cr particles, Nb flakes or Nb particles and Ta particles with a purity of not less than 99.9%. Remove the oxide film and oil stains from the surface of the raw materials by mechanical grinding and ultrasonic cleaning with anhydrous ethanol. After drying, weigh and batch the raw materials according to the measured purity and target composition.
[0033] Step 2, Pre-alloying of refractory elements: Approximately 10% of the total Cu mass is placed together with all Cr, Nb, and Ta in a water-cooled copper crucible in a vacuum arc melting furnace. The furnace cavity is evacuated to a vacuum level not exceeding 1 × 10⁻⁶. -3 Pa was used to fill the furnace with high-purity Ar, and the vacuum-filling-Ar operation was repeated three times. For the first pre-melting, the arc power was increased in a stepped manner; under reliable temperature measurement conditions, the reference temperature of the molten pool surface was successively raised to approximately 1200 ℃, 1500 ℃, and 1880 ℃, and held for approximately 10 s, 10 s, and 20–40 s respectively, until the macroscopic Nb and Ta particles essentially disappeared and the molten pool was continuous and uniformly flowing. After arc cessation, the pre-alloyed ingot was allowed to completely solidify on a water-cooled copper crucible inside the furnace. The pre-alloyed ingot was then flipped and remelted four times, with the reference temperature of the molten pool surface controlled at 1820–1850 ℃ each time, and held for 20–30 s after forming a complete molten pool. After each remelting, it was completely solidified on a water-cooled copper crucible; the pre-alloying stage involved a total of five melting processes.
[0034] Step 3: Add the remaining Cu and fuse them together. Place the pre-alloyed ingot and approximately 90% of the remaining Cu into a water-cooled copper crucible. First, raise the reference temperature of the molten pool surface to approximately 1200 °C and hold for 10 seconds to fully melt the Cu. Then raise it to approximately 1450 °C and hold for 5 seconds, followed by raising it to approximately 1750 °C. After the pre-alloyed ingot and Cu form a uniform and continuous molten pool, hold it for 20–30 seconds and allow it to completely solidify on the water-cooled copper crucible. Then, remelt the ingot six times, controlling the reference temperature of the molten pool surface at 1680–1725 °C each time, gradually reducing the arc power in subsequent remeltings. After each complete molten pool is formed, hold it for 20–30 seconds, ensuring complete solidification on the water-cooled copper crucible. The fusion stage involves a total of seven melting cycles. The temperatures mentioned above are reference temperatures of the molten pool surface under non-contact temperature measurement conditions. Actual melting is controlled by the disappearance of macroscopic unmelted blocks and the complete and continuous molten pool.
[0035] Step 4, warm rolling deformation: Grind or machine the surface of the ingot to remove the oxide layer and defects, and round the edges. Heat the ingot to 350 ℃ and hold it until the temperature is uniform before performing multiple warm rolling passes, with a reduction rate of approximately 10% per pass. After each rolling pass, immediately return the ingot to the furnace and hold it at 350 ℃ for 3–5 minutes before proceeding to the next rolling pass. Rolling is completed when the cumulative total reduction rate reaches approximately 70%. After final rolling, cool the ingot to room temperature using water cooling.
[0036] Step 5, aging heat treatment; the warm rolled plate is placed in a vacuum heat treatment furnace and held at 500 ℃ for 1 h, and then water-cooled to room temperature to obtain Cu-2.60Cr-2.01Nb-0.50Ta tantalum-containing high-strength and high-conductivity copper alloy. Example 2
[0037] This embodiment provides a method for preparing a tantalum-containing high-strength, high-conductivity copper alloy. The raw materials are proportioned by mass percentage as follows: Cu 94.94%, Cr 2.60%, Nb 2.06%, and Ta 0.40%. In this composition, R is 2.051, and the nominal atomic fraction of Ta in (Nb+Ta) is 9.07 at.%. Except for the different composition, the raw material processing, pre-alloying of refractory elements, addition of residual Cu for melting, warm rolling, and vacuum aging at 500 ℃ / 1 h are all the same as in Example 1, resulting in a Cu-2.60Cr-2.06Nb-0.40Ta tantalum-containing high-strength, high-conductivity copper alloy. Example 3
[0038] This embodiment provides a method for preparing a tantalum-containing high-strength, high-conductivity copper alloy. The raw materials are proportioned by mass percentage as follows: Cu 94.24%, Cr 3.00%, Nb 2.46%, and Ta 0.30%. In this composition, R is 2.051, and the nominal atomic fraction of Ta in (Nb+Ta) is 5.89 at.%. Except for the different composition, the raw material processing, pre-alloying of refractory elements, addition of residual Cu for melting, warm rolling, and vacuum aging at 500 ℃ / 1 h are all the same as in Example 1, resulting in a Cu-3.00Cr-2.46Nb-0.30Ta tantalum-containing high-strength, high-conductivity copper alloy.
[0039] Comparative Example 1 This comparative example provides a Ta-free Cu-Cr-Nb alloy with the following raw material composition by mass percentage: Cu 93.85%, Cr 3.25%, and Nb 2.90%. The atomic ratio of Cr to Nb in this composition is 2.002, and the total Cr and Nb content is 6.15%. Except for the absence of Ta in the pre-alloying stage, the vacuum arc melting, ingot remelting, 350 °C warm rolling, and 500 °C / 1 h vacuum aging processes are identical to those in Example 1, used to evaluate the changes in alloy properties after introducing Ta and reducing the total Cr and Nb content.
[0040] Comparative Example 2 This comparative example provides a tantalum-containing Cu-Cr-Nb-Ta alloy with a relatively high Cr / (Nb+Ta) atomic ratio. The raw materials are formulated as follows by mass percentage: Cu 94.9445%, Cr 2.60%, Nb 1.9555%, and Ta 0.50%. In this composition, the atomic ratio R of Cr to (Nb+Ta) is 2.100, the nominal atomic fraction of Ta in (Nb+Ta) is 11.60 at.%, and the total content of Cr+Nb+Ta is 5.0555%. Except for the different composition, the raw material treatment, pre-alloying of refractory elements, addition of residual Cu for fusion, warm rolling, and vacuum aging at 500℃ / 1 h are all the same as in Example 1, used to evaluate the effect of increasing the Cr / (Nb+Ta) atomic ratio from approximately 2.05 to 2.10 on the overall matching of alloy strength and thermal conductivity.
[0041] Test methods and performance results: Performance tests were conducted on the plates of the examples and comparative examples after aging at 500 ℃ / 1 h and water cooling, under the same sampling direction and sample conditions. Room temperature tensile tests were conducted according to GB / T 228.1—2021, and high-temperature tensile tests at 600 ℃ were conducted according to GB / T 228.2—2015; thermal conductivity at room temperature and 600 ℃ was tested according to GB / T22588—2008. The test results are shown in Table 1. In Table 1, YS represents yield strength, and UTS represents tensile strength; unless otherwise specified, all data in the table are expressed as aged at 500 ℃ / 1 h.
[0042] As can be seen from the above examples and comparative examples, the total content of Cr, Nb, and Ta in Example 1 is 5.11%, which is about 16.9% lower than that in Comparative Example 1. Its room temperature yield strength and tensile strength decrease by about 4.7% and 3.6%, respectively, but its room temperature thermal conductivity increases by about 3.5%; at 600 °C, the yield strength, tensile strength, and thermal conductivity increase by about 5.2%, 4.4%, and 3.7%, respectively. This result indicates that Example 1 can still achieve a good match between strength and thermal conductivity at 600 °C even with a significant reduction in the total alloying content. The total content of Cr, Nb, and Ta in Example 2 is 5.06%, which is about 17.7% lower than that in Comparative Example 1. Its room temperature yield strength and tensile strength decrease by only about 1.6% and 1.8%, respectively, while its room temperature thermal conductivity increases by about 1.0%; at 600 °C, the yield strength, tensile strength, and thermal conductivity increase by about 0.7%, 1.3%, and 1.3%, respectively, exhibiting a more balanced overall performance. The total Cr, Nb, and Ta content of Example 3 was 5.76%, which was approximately 6.3% lower than that of Comparative Example 1. Its room temperature yield strength and tensile strength increased by approximately 4.3% and 2.8%, respectively, and its yield strength and tensile strength at 600 °C increased by approximately 11.9% and 6.3%, respectively. Its thermal conductivity at room temperature and at 600 °C decreased by approximately 2.2% and 1.7%, respectively, but remained at 305 W·m. -1 ·K -1 and 296 W·m -1 ·K -1This is suitable for applications requiring higher high-temperature load-bearing capacity. Furthermore, Comparative Example 2 has a total Cr, Nb, and Ta content of 5.0555%, close to the 5.11% of Example 1, and the Ta content is the same, but the atomic ratio of Cr to (Nb+Ta) increases from approximately 2.05 to 2.10. Compared to Example 1, Comparative Example 2 shows an increase of approximately 1.6% and 1.1% in room temperature yield strength and tensile strength, respectively, and an increase of approximately 1.6% and 1.1% in yield strength and tensile strength at 600 °C, respectively; simultaneously, the thermal conductivity at room temperature and at 600 °C decreases by approximately 8.6% and 13.1%, respectively. This trend indicates that when the Cr / (Nb+Ta) atomic ratio is increased to 2.10, a slightly Cr-rich state may provide some strengthening effect, but it sacrifices some thermal conductivity, and its overall strength-thermal conductivity match is not as good as Example 1 with an R of approximately 2.05. In summary, under the condition that the atomic ratio R of Cr to (Nb+Ta) is approximately 2.05, by synergistically adjusting the total amount of Cr and Nb and the nominal atomic fraction of Ta in (Nb+Ta), tantalum-containing Cu-Cr-Nb alloys with biased thermal conductivity, overall balance, and strength can be obtained, respectively. Compared with the comparative example without Ta, the composition and preparation process defined in this invention can improve the overall match between strength and thermal conductivity at 600 °C while reducing or controlling the total alloying content. Although a small strength gain can be obtained when R is increased to 2.10, the thermal conductivity decreases, further indicating that R of approximately 2.05 is more conducive to obtaining an overall balance between strength and thermal conductivity.
[0043] In the description of the above embodiments, specific features, structures, materials, or characteristics may be combined in any suitable manner in one or more embodiments or examples.
[0044] The above description is merely a specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention should be included within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be determined by the scope of the claims.
Claims
1. A high-strength, high-conductivity copper alloy containing tantalum, characterized in that, Included by weight percentage: The alloy contains 2.60 to 3.00 wt.% chromium, 2.00 to 2.50 wt.% niobium, and 0.30 to 0.50 wt.% tantalum, with the balance being copper and unavoidable impurities. The atomic ratio of chromium to the sum of niobium and tantalum is 2.00 to 2.10, and the atomic fraction of tantalum in the sum of niobium and tantalum is 0.05 to 0.
12.
2. The tantalum-containing high-strength, high-conductivity copper alloy according to claim 1, characterized in that, The total content of chromium, niobium, and tantalum is 5.00~5.80 wt.%; The strengthening phase in the alloy is a Cr2(Nb,Ta) type composite Laves phase.
3. The tantalum-containing high-strength, high-conductivity copper alloy according to claim 1, characterized in that, The atomic ratio of chromium to the sum of niobium and tantalum is 2.03 to 2.
07.
4. A method for preparing a tantalum-containing high-strength, high-conductivity copper alloy, characterized in that, The preparation of the tantalum-containing high-strength, high-conductivity copper alloy according to any one of claims 1 to 3 comprises: Weigh out the raw materials of copper, chromium, niobium and tantalum according to the proportions; Take 5-15% of the total mass of copper and melt it with all chromium, niobium and tantalum, and solidify it. Turn the resulting pre-alloyed ingot over and melt it again 3-4 times to obtain the pre-alloyed ingot. The pre-alloyed ingot is melted together with the remaining copper and solidified. The resulting ingot is then flipped over and melted repeatedly 5 to 6 times to obtain the final ingot. The ingot is subjected to multiple warm rolling passes at 300~450℃ to obtain warm rolled sheet; The warm-rolled sheet is subjected to aging heat treatment at 450~550℃, held at that temperature for 0.5~4h, and then rapidly cooled to room temperature to obtain the tantalum-containing high-strength and high-conductivity copper alloy.
5. The method for preparing a tantalum-containing high-strength, high-conductivity copper alloy according to claim 4, characterized in that, The total content of chromium, niobium and tantalum in the tantalum-containing high-strength and high-conductivity copper alloy is 5.00~5.80 wt.%; the strengthening phase in the alloy is a Cr2(Nb,Ta) type composite Laves phase.
6. The method for preparing a tantalum-containing high-strength, high-conductivity copper alloy according to claim 4, characterized in that, When 5-15% of the total copper mass is smelted with all chromium, niobium and tantalum, the arc power is increased in a stepwise manner during smelting. The reference temperatures of the molten pool surface are 1150-1250℃, 1450-1550℃ and 1800-1900℃ respectively, and are maintained for 5-15 seconds, 5-15 seconds and 20-40 seconds respectively.
7. The method for preparing a tantalum-containing high-strength, high-conductivity copper alloy according to claim 4, characterized in that, The fusion process employs a stepped heating method, with the reference temperatures on the surface of the molten pool being 1150~1250℃, 1400~1500℃, and 1650~1780℃ respectively; during the last 1~2 remelting cycles, the reference temperature on the surface of the molten pool is controlled at 1650~1720℃.
8. The method for preparing a tantalum-containing high-strength, high-conductivity copper alloy according to claim 4, characterized in that, The single-pass reduction rate of the multi-pass warm rolling is 5~12%, and the total reduction rate is 60~75%. After each pass rolling, the rolls are returned to the furnace for heat preservation for 3~5 minutes. The temperature of the warm rolling is 300~450℃.
9. The method for preparing a tantalum-containing high-strength, high-conductivity copper alloy according to claim 4, characterized in that, The rapid cooling is water cooling; the aging heat treatment is carried out in a vacuum or inert atmosphere.
10. The application of the tantalum-containing high-strength and high-conductivity copper alloy prepared by any one of claims 1 to 3 or any one of claims 4 to 9 in the regenerative cooling combustion chamber lining of a liquid rocket engine or in high heat flux density components at 500~700°C.